Cerebral Hemorrhage: Pathophysiology, Treatment, and Future Directions. Issue 8 (15th April 2022) - Magid-Bernstein, Jessica; Girard, Romuald; Polster, Sean; Srinath, Abhinav; Romanos, Sharbel; Awad, Issam A.; Sansing, Lauren H.
Abstract : Intracerebral hemorrhage (ICH) is a devastating form of stroke with high morbidity and mortality. This review article focuses on the epidemiology, cause, mechanisms of injury, current treatment strategies, and future research directions of ICH. Incidence of hemorrhagic stroke has increased worldwide over the past 40 years, with shifts in the cause over time as hypertension management has improved and anticoagulant use has increased. Preclinical and clinical trials have elucidated the underlying ICH cause and mechanisms of injury from ICH including the complex interaction between edema, inflammation, iron-induced injury, and oxidative stress. Several trials have investigated optimal medical and surgical management of ICH without clear improvement in survival and functional outcomes. Ongoing research into novel approaches for ICH management provide hope for reducing the devastating effect of this disease in the future. Areas of promise in ICH therapy include prognostic biomarkers and primary prevention based on disease pathobiology, ultra-early hemostatic therapy, minimally invasive surgery, and perihematomal protection against inflammatory brain injury.